Biomechanical Properties of Pinang Jawa (Pinanga javana): Structural Performance and Ecological Significance - zulkarnaen, rizmoon; Adik Bahanawa; Hendra Helmant; Deanova Frestiana Br. Pelawi; Nabela Fikriyy (Journal of Sylva Indonesiana, 2025)
The mechanical strength of Pinang Jawa (Pinanga javana), an endemic palm species in Java, is essential for understanding its structural resilience and ecological role. This study characterizes its biomechanical properties by evaluating the modulus of rupture (MOR) and the modulus of elasticity (MOE) using standardized three-point bending tests. Samples were collected sustainably from mature palms on Mount Slamet, ensuring minimal ecological disruption. Results indicate that the MOR ranged from 7.78 to 14.47 MPa, with a mean of 11.24 MPa (±2.19 MPa), and MOE values spanned from 440.82 to 792.95 MPa, averaging 572.17 MPa (±89.48 MPa). Statistical analysis, including 95% confidence intervals of [9.77, 12.71] MPa for MOR and [512.06, 632.28] MPa for MOE, confirmed the reliability of these estimates. A one-way ANOVA revealed significant variability in MOE (p < 0.05), attributed to the anisotropic nature and heterogeneous fiber orientation, while MOR showed less pronounced variability (p > 0.05), suggesting consistent rupture resistance. These findings highlight the stem’s moderate mechanical properties compared to other palms and provide insights into its structural adaptations. This study enhances the understanding of Pinang Jawa’s biomechanical behavior, reinforcing its ecological significance as an endemic species and supporting further research on palm biomechanics and conservation strategies